Effect of the switching layer on CBRAM reliability and benchmarking against OxRAM devices. (October 2021) - Belmonte, A.; Reale, G.; Fantini, A.; Radhakrishnan, J.; Redolfi, A.; Devulder, W.; Nyns, L.; Kundu, S.; Delhougne, R.; Goux, L.; Kar, G.S.
Highlights: Thorough CBRAM/OxRAM reliability benchmarking. Optimization of CBRAM switching conditions for endurance boost. Effect of CBRAM switching layer on programming energy and memory window. Revealing which technology is more suitable for long data retention and endurance. Abstract: We thoroughly benchmark the reliability of Cu-based CBRAM stacks with different switching layers against state-of-the-art OxRAM stacks. We optimize the switching conditions for maximizing the endurance lifetime in three CBRAM stacks, outlining the impact of the switching layer on the energy required for the switching operation and on the memory window. We show that CBRAM provide a larger memory window than OxRAM, but the switching energy is systematically higher, and the endurance lifetime is shorter. We also demonstrate that the larger memory window of CBRAM degrades over time and is thus only an apparent advantage with respect to OxRAM. Therefore, this study reveals that OxRAM devices investigated in this work are more suitable candidates than for applications targeting long data retention and low programming voltage.